2018
DOI: 10.21053/ceo.2018.00052
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hearing Aid Digital Noise Reduction and Directionality on Acceptable Noise Level

Abstract: Objectives Two main digital signal processing technologies inside the modern hearing aid to provide the best conditions for hearing aid users are directionality (DIR) and digital noise reduction (DNR) algorithms. There are various possible settings for these algorithms. The present study evaluates the effects of various DIR and DNR conditions (both separately and in combination) on listening comfort among hearing aid users.Methods In 18 participants who received hearing aid fitting services from the Rehabilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A study specified that individuals with hearing loss experience increased cognitive load and listening effort when the SNR is poor [13]. A study utilising the Acceptable Noise Level (ANL) as a subjective measure to assess the listening comfort of individuals who underwent hearing aid fitting services was conducted by a number of researchers [7], [14]. A fully integrated system-on-chip (SoC) hearing aid, which offered the potential for precise and adaptive gain control, enhancing the performance and user experience of hearing aids was also developed in the course of further research activities [15].…”
Section: Bolarinwa and Ayomamentioning
confidence: 99%
“…A study specified that individuals with hearing loss experience increased cognitive load and listening effort when the SNR is poor [13]. A study utilising the Acceptable Noise Level (ANL) as a subjective measure to assess the listening comfort of individuals who underwent hearing aid fitting services was conducted by a number of researchers [7], [14]. A fully integrated system-on-chip (SoC) hearing aid, which offered the potential for precise and adaptive gain control, enhancing the performance and user experience of hearing aids was also developed in the course of further research activities [15].…”
Section: Bolarinwa and Ayomamentioning
confidence: 99%
“…An omnidirectional microphone was set for all participants, and other digital signal processing algorithms (such as Sound Smoothing, eWind Screen, and Feedback Stopper) were inactivated. Based on the protocol introduced by Shahid Beheshti University of Medical Sciences (BUMS) for fitting the digital processing hearing aid, each participant was evaluated using the calibrated version of the Ling-6 sounds for evaluation of aided detection thresholds [16][17][18]. Despite the fact that DIN test was accomplished in suprathreshold level, the hearing aid was fitted so that the Ling-6 sounds were audible and discriminative in the level of 30 dB HL to provide equal audibility for all subjects.…”
Section: Hearing Aid Fittingmentioning
confidence: 99%
“…In addition, it has been shown that ANL can be a good predictor of hearing aid satisfaction; people with lower ANL have better suppression in the auditory efferent system and usually are more satisfied with their hearing aids [8]. The lower ANL indicates better noise tolerance [8][9][10][11][12][13]. The Persian version of this test was validated by Ahmadi et al using a running female-talker story with a 12-talker babble in children [12].…”
Section: Introductionmentioning
confidence: 99%
“…The lower ANL indicates better noise tolerance [8][9][10][11][12][13]. The Persian version of this test was validated by Ahmadi et al using a running female-talker story with a 12-talker babble in children [12]. ANL test has been investigated just for the adults with CI [14] and it has not been yet applied for children with CI, especially for bimodal hearing.…”
Section: Introductionmentioning
confidence: 99%